Sustainable Development Goals: Challenge or Priority? (GESTIÓN Y TENDENCIAS, 2020)
The article provides an overview of the global "SDG Challenge" report, which takes the temperature of organizations worldwide with respect to the Sustainable Development Goals (SDGs). It also presents the results for Chilean companies, which are compared with the global SDG results.